Kontribusi Manajemen Fungsional dalam Implementasi Strategi Perusahaan terhadap Pencapaian Kinerja Perusahaan Manufaktur Berdasarkan Pendekatan Balanced Scorecard (Survey Pada Perusahaan Manufaktur Berskala Besar di Kota Surabaya) - -, Gunarianto - (Jurnal Manajemen Akuntansi dan Bisnis, 2008)
The purpose of this research is to analyze the contribution of functional management in the implementation of firm strategy which consists of 1) production management, 2) marketing management, 3) financial management, 4) research and development, and 5) human resources management toward the achievement of firm performance based on Balanced Scorecard approach both simultaneously and partially. This research was carried out on large scale manufacture firms in Surabaya. The data collecting was carried out by spreading questionnaires to five functional managers in technical method of simple random sampling. The population in this research are 83 large scale manufacture firms. There are 45 firms used as samples analyzed by using Yamane formula and precision of 10 %. The writer use regression analysis model to analyze data and test the hypothesis. The result of this research and hypothesis testing show that 1) simultaneously, functional management in the implementation of firm strategy gives positive contribution to performance achievement of manufacture firms based on balanced scorecard approach, 2) Partially functional management consist of: 1) production management, 2) marketing management, 3) financial management, 4) research and development, and 5) human resources management in the implementation of firm strategy gives positive and significant contribution to performance achievement of manufacture firm based on the balanced scorecard approach Keywords: Performance, Strategy, Balanced Scorecard.